Ophiopogon japonicus—A phytochemical, ethnomedicinal and pharmacological review. (2nd April 2016) - Chen, Min-Hui; Chen, Xiao-Jia; Wang, Mei; Lin, Li-Gen; Wang, Yi-Tao
Abstract: Ethnopharmacological relevance: Ophiopogonis Radix (Maidong in Chinese), the root of Ophiopogon japonicus, is widely used in local medicines of China, Japan and some south-eastern Asian countries. According to the traditional Chinese medicine (TCM) principle, Ophiopogonis Radix nourishes the yin, promotes body fluid production, moistens the lung, eases the mind and clears away heart fire. This review summarizes the achievements of the investigations in botany, phytochemistry, quality control, traditional uses, pharmacological activities and clinical studies on O. japonicus ; this review also describes the shortcomings of studies on this herbal drug and thus serves as the basis of further scientific research and development of this traditional herbal drug. Materials and methods: O. japonicus -related information was collected from various resources, including books on Chinese herbs and the Internet databases, such as Google Scholar, SciFinder, Web of Science, Elsevier, ACS, PubMed and China Knowledge Resource Integrated (CNKI). Results: O. japonicus is widely distributed in East Asia, especially in China. Numerous compounds were identified from this plant. The main components of O. japonicus include steroidal saponins, homoisoflavonoids and polysaccharides, which exhibited various pharmacological activities, such as cardiovascular protection, anti-inflammation, anticancer, anti-oxidation, immunomodulation, cough relief, antimicrobial, and anti-diabetes. Conclusions: O. japonicus is a common traditional Chinese herbal drug used as the main ingredient in many prescriptions. Modern researches verified that O. japonicus can be used either as a healthy food or a therapeutic agent for disease prevention and treatment. The molecular mechanisms and chemical principles of this herbal medicine should be further explored. Graphical abstract: